Design, implementation and analysis of wearable biomedical assistance device for elderly. (2017) - Sabitha, Ramakrishnan; Sukanya, Sekar; Piranava, Tamilselvan
In this era, there is an increase in the number of elderly people living alone and also in the number of injuries and deaths due to unavailability of help around them. Here, we aim to design a wearable device for the elderly that will sense their most common troubles and alert their family in case of a peril. Few common problems faced by elderly, the ill-effects of which can be greatly reduced if addressed immediately, include fall and arrhythmia. The assistance device developed by us monitors a person's movements using a triaxial accelerometer to detect falls. It also monitors the person's ECG to detect arrhythmia condition. The device is programmed to alert the concerned person automatically if either or both of these conditions occur.